2019
DOI: 10.18316/rca.v13i2.5966
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Viability for Material Developed From Coal Bottom Ash for Highways Under Construction

Abstract: e increase of the quality of life of the contemporary Man also leads to the increase of the generation of energy. Many alternative sources of energy have been explored, but coal is still an important input, contributing around 29% of the world's energy matrix, despite environmental controversies about its use. Its burning in thermal plants generates the solid bottom ash residue, a material with little application and with potential to generate environmental damages in the places where they accumulate. e Southe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…The result showed in this table is close to that found in the work developed by Sabedot et al [10] where the phases identified in the diffractogram were silica and mullite. The results prove that the CCP's components are phases of great potential for incorporation as a reinforcement phase in ceramic specimens.…”
Section: X-ray Diffractionsupporting
confidence: 91%
“…The result showed in this table is close to that found in the work developed by Sabedot et al [10] where the phases identified in the diffractogram were silica and mullite. The results prove that the CCP's components are phases of great potential for incorporation as a reinforcement phase in ceramic specimens.…”
Section: X-ray Diffractionsupporting
confidence: 91%